1994
DOI: 10.1056/nejm199401203300302
|View full text |Cite
|
Sign up to set email alerts
|

Residential Radon Exposure and Lung Cancer in Sweden

Abstract: Residential exposure to radon is an important cause of lung cancer in the general population. The risks appear consistent with earlier estimates based on data in miners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
125
1
2

Year Published

1995
1995
2014
2014

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 307 publications
(141 citation statements)
references
References 22 publications
11
125
1
2
Order By: Relevance
“…A first report of a large-scale study on indoor radon and lung cancer in Sweden involved 1360 lung cancer cases and 2847 controls (63). Similar to earlier studies, it showed a moderate but significant effect of indoor radon on lung cancer with an odds ratio of 1.3 for a time-weighted exposure at 140 to 400 Bq/m3 and 1.8 at levels above 400 Bq/m3 of radon gas.…”
Section: Studies Of Indoor Radon and Lung Cancersupporting
confidence: 54%
“…A first report of a large-scale study on indoor radon and lung cancer in Sweden involved 1360 lung cancer cases and 2847 controls (63). Similar to earlier studies, it showed a moderate but significant effect of indoor radon on lung cancer with an odds ratio of 1.3 for a time-weighted exposure at 140 to 400 Bq/m3 and 1.8 at levels above 400 Bq/m3 of radon gas.…”
Section: Studies Of Indoor Radon and Lung Cancersupporting
confidence: 54%
“…Among them, most were excluded after abstract because they were occupational studies on miners, no case control studies, no relevant exposure or endpoint, and reviews. After assessing the full-text of the 38 relevant articles, we identified 22 eligible studies for meta-analysis (Blot et al, 1990;Schoenberg et al, 1990;Pershagen et al,1992Pershagen et al, , 1994Alavanja et al, 1994Alavanja et al, , 1999Létourneau et al, 1994;Auvinen et al, 1996;Ruosteenoja et al, 1996;Darby et al, 1998;Field et al, 2000;Sobue et al, 2000;Lagarde et al, 2001;Pisa et al, 2001;Barros-Dios et al, 2002;Wang et al, 2002;Baysson et al, 2004;Bochicchio et al, 2005;Wichmann et al, 2005;Sandler et al, 2006;Thompson et al, 2008;Wilcox et al, 2008). Seven studies were excluded for previous mete-analysis (Lubin and Boice, 1997;Pavia et al, 2003) and combined analysis in Europe, North America or China Darby et al, 2005;Krewski et al, 2005;Wang et al, 2005;Darby et al, 2006).…”
Section: Literature Searchmentioning
confidence: 99%
“…The three risk factor combinations presented in Study 1 have all been found, in practice, to present synergistic risks: alcohol-driving (Cherpitel, Tam, Midanik, Caetano, & Greenfield, 1995; Institute for Alcohol Studies, 2010; Office for National Statistics, 2009), aspirinclopidogrel (Delaney, Opatrny, Brophy, & Suiss, 2007;Hallas et al, 2006) and radon-tobacco (Barros-Dios et al, 2002;Darby et al, 2005;Pershagen et al, 1994). 1 These combinations were selected to provide a set of synergistic risk combinations that were each likely to be of different degrees of familiarity to the participants and, therefore, could facilitate an assessment of the extent to which prior knowledge/experience of the combination would influence the participant's risk model judgements.…”
Section: Designmentioning
confidence: 98%